PERSEPSI DOSEN TERHADAP INTEGRASI PENDIDIKAN KARAKTER PADA MATAKULIAH KEILMUAN DAN KETERAMPILAN (MKK) BIDANG BOTANI DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Wan Syafi’i; Mariani Natalina; Wilda Farida (Program Studi Pendidikan Biologi, 2013)
This research aims to determine the perceptions of lecturer towards the integration of character education in the groups MKK botany at the Biology Education Program Faculty of Education University of Riau. The sample in this research is lecturer’s in MKK botany taken by total sampling. The data technique collecting is perception questionaires to determine lecturer perceptions of the integration of character education and tests to determine lecturer understanding. The results showed that the perception of lecturer through perception questionaire for each sub-indicators definition of character, the function of character education, the goal of character education, the scope of character education, the implementation of character education and the character education in university is very good, while understanding the character education of lecturer’s is very good. The conclusions in this research is perceptions of lecturer towards the integration of character education in the groups MKK botany is very good.Keywords: Character Education, MKK Botany, Perception.